Perancangan Sistem Informasi Akademik pada SD Holistic Children Center Berbasis Web - Tumanggor, Ika Lestari; Jamaluddin, Jamaluddin; Lumbantoruan, Gortap (Universitas Methodist Indonesia, 2024)
In an increasingly competitive educational landscape, many institutions are seeking technologies that enhance performance. An academic information system is a system developed to manage academic data using computer technology, transforming academic processes into useful information. This research aims to design a web-based academic information system at Holistic Children Center Elementary School. Currently, the management of academic data at the school is conducted manually using books and Microsoft Excel, which is prone to data loss and inefficient in tracking academic information. The implementation of an academic information system with a centralized database method is expected to improve the effectiveness and efficiency of academic data management and support the enhancement of the school's accreditation. The research methods employed include direct observation, interviews with school officials, and literature studies to obtain relevant theories and methods. The results indicate that the designed academic information system can manage data centrally and structurally, facilitating information presentation for teachers, students, and parents. Additionally, this system can enhance the school's reputation through more organized and integrated data management and simplify the tracking and documentation of alumni.